The relationship between serum monoterpene levels and bone health: a retrospective cross-sectional analysis from the National Health and Nutrition Examination Survey (NHANES) data - Yu-Wei Fang; Yu-Wei Fang; Chi-Kang Wang; Chien-Yu Lin; Chien-Yu Lin; Chien-Yu Lin (Frontiers Media S.A., 2024)
IntroductionMonoterpenes, a subset of the terpene family composed of two isoprene units, have garnered significant attention in research circles owing to their potential medicinal benefits. Recent experimental studies indicate that they might exert positive effects on bone health. Nevertheless, the impact of monoterpenes exposure on bone health remains unexplored in humans.MethodsWe examined 748 adults (age ≥ 40 years) from the National Health and Nutrition Examination Survey (NHANES) 2013-2014 to explore the correlation between three monoterpenes (α-pinene, β-pinene, and limonene), bone mineral density (BMD) in the total lumbar spine and proximal femur, FRAX® scores, and prior bone fracture history.Results and discussionOur analysis unveiled a significant inverse association between a one-unit increase in the natural logarithm (ln) of α-pinene and limonene and total proximal femur BMD (ß = −0.027, S.E. = 0.008, P = 0.004 and ß = −0.019, S.E. = 0.007, P = 0.016, respectively). As serum α-pinene levels ascended across quintiles, there was a notable decrease in total proximal femur BMD (P for trend = 0.025). The inverse relationship between ln α-pinene levels and total proximal femur BMD was more pronounced in women, especially pre-menopausal women. Compared to subjects with α-pinene and limonene levels at or below the 50th percentiles, those exceeding this threshold exhibited the lowest mean value of total proximal femur BMD (0.8628 g/cm2, S.E. = 0.026, P = 0.009). However, the trend was not statistically significant (P = 0.070). Additionally, all three monoterpenes were linked to a higher prevalence of previous spine fractures, whereas β-pinene showed a reduced incidence of other types of fractures. In this comprehensive survey of American adults aged 40 and above, higher serum levels of α-pinene and limonene correlated with decreased total proximal femur BMD. Furthermore, our findings suggest a potential combined effect of α-pinene and limonene on total proximal femur BMD. Further investigation is essential to elucidate the clinical relevance and causative nature of our findings.